Auditors and job stress: evidence from Malaysia - Mustapha, Mazlina; Ismail, Hashanah; Ismail, Juniza (2013)
This paper attempts to explore the factors that caused the stress among the auditors in Malaysia. Among the factors examined are the nature of auditors' job, their relationship at the workplace, the behavior of the auditors and gender. Data used in the study was collected using primary source. About ISO questionnaires were distributed to auditors in Klang Valley. However, only 71 questionnaires were completed and usable for the purpose of the study. The results show that their relationship at the work place and the auditors' behavior significantly affect their stress level. The fact that audit job demand various experience and knowledge, and need their high commitment, are rank highest among the factors that lead to their stress. The nature of audit job which require the auditors to deal with all kind of people with different behavior and the fact that they are always doing different things from time to time cause the auditors to be very stressful. However, the respondents agree that their stress level depends on how they perceived those situations. This study provides information to the public accounting firms to better understand their employees and help them to arrange programs to manage job stress among the employees, and further reinstate and motivate them in their job.